PENGARUH BERMAIN LEGO KONSTRUKTIF TERHADAP KECERDASAN VISUAL SPASIAL ANAK USIA DINI KELOMPOK A DI RAUDHATUL ATHFAL (RA) DARUL MUQOMAH BULUNG KULON JEKULO KUDUS TAHUN 2019/2020 - Muhammad Sajudin; Nur Habibah (Jurnal Studi Islam dan Sosial, 2021)
The Influence of Lego Constructive Games on the Spatial Visual Intelligence of Early Childhood Group A in RA Darul Muqomah Bulung Kulon Jekulo Kudus in 2019/2020. Constructive play is a game that creates, creates, shapes, and builds something, product, work or creation using physical objects such as blocks, crayons, bricks, plasticine, dough (flour dough), clay, sand , lego, paint, crayons and markers by symbolically representing the ideas that are in the child's mind. Playing using lego can provide a stimulus to early childhood to develop their visual spatial intelligence, because by using constructive lego, children will be interested in playing and describing the ideas that are in their mind into three-dimensional objects according to the child's imagination. From here, children are able to improve their spatial visual intelligence. This study aims to determine the effect of lego constructive play on spatial visual intelligence of early childhood group A in RA Darul Muqomah Kudus. The approach used is a quantitative approach with the type of pre-experimental research with the design of One Group Pretest-Posttest Design. The subjects of this study were all group A in RA Darul Muqomah Kudus, totaling 33 students. This study uses data collection methods, namely tests, observation, documentation and tests. The data analysis method used is the normality test and hypothesis testing. The results obtained are the average pretest and posttest of early childhood visual spatial intelligence has a difference of 4.94, and the average posttest score is higher than the average pretest score. The results of the Paired Sample T-test analysis showed a significant value of 0.000 <0.05. In accordance with the criteria if the significant value <0.05 means that Ho is rejected and Ha is accepted. Thus it can be concluded that the constructive lego game affects the spatial visual intelligence of early childhood group A in RA Darul Muqomah Kudus.